1982
DOI: 10.1116/1.571362
|View full text |Cite
|
Sign up to set email alerts
|

Effect of x-ray flux on polytetrafluoroethylene in x-ray photoelectron spectroscopy

Abstract: The effect of the x-ray flux in x-ray photoelectron spectroscopy (XPS) on the constitution of the polytetrafluoroethylene (PTFE) surface has been examined. The radiation dose rate for our specimen was ∠107 rad/s. We observed the structure, magnitude and binding energy of the C(1s) and F(1s) features of the XPS spectrum and the mass spectrum of gaseous species evolved during irradiation. The strong time dependence of these signals over a period of several hours indicated that the surface constitution of PTFE is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

1987
1987
2006
2006

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(49 citation statements)
references
References 0 publications
2
47
0
Order By: Relevance
“…Such 2 Because degradation occurs under relatively mild conditions, it is always necessary to assure that the sample does not degrade significantly during data accumulation. [1][2][3] These studies showed that degradation proceeded in a similar fashion for all the Teflons so far mentioned, as follows: the scission of COC and COF bonds led to graphitization, crosslinking, and the loss of low-molecular weight species, as revealed by mass spectrometry. A decrease was seen in the amount of CF 2 , as was a gain in the amount of CF 3 ; this means that CF 2 • must have reacted with F• to produce substantial amounts of CF 3 .…”
Section: Introductionmentioning
confidence: 82%
“…Such 2 Because degradation occurs under relatively mild conditions, it is always necessary to assure that the sample does not degrade significantly during data accumulation. [1][2][3] These studies showed that degradation proceeded in a similar fashion for all the Teflons so far mentioned, as follows: the scission of COC and COF bonds led to graphitization, crosslinking, and the loss of low-molecular weight species, as revealed by mass spectrometry. A decrease was seen in the amount of CF 2 , as was a gain in the amount of CF 3 ; this means that CF 2 • must have reacted with F• to produce substantial amounts of CF 3 .…”
Section: Introductionmentioning
confidence: 82%
“…The surface-treatment solution was prepared with hexane (guaranteed reagent; Kanto Chemicals) at a concentration of 0.1 mol l 1 . Highly polished silicon wafers with a naturally oxidized layer were used as the solid substrates for silane treatment.…”
Section: Experimental Preparation Of Organic Silane Monolayers On Silmentioning
confidence: 99%
“…It was the aim of this article to have been reported on X-ray-induced damage in examine the effect of the X-rays in XPS on the XPS analysis on different polymers. [3][4][5] In the case constitution of the PVDF surface using a specof polytetrafluoroethylene (Teflon), Wheeler and trometer with a nonmonochromatic MgKa X-ray Pepper, 4 using a nonmonochromatic MgKa X-ray source. We observed the time dependence of the source, showed that the polymer surface is deflushape, intensity, and binding energy of the C 1s orinated by X-rays rather than by electron bomand F 1s lines in the XPS spectrum, trying to unbardment used for the compensation of the surderstand the damage-responsible mechanism.…”
Section: Introductionmentioning
confidence: 99%